Anpassning för personer med funktionsnedsättning i arbetslivet - Arbetsgivarens ansvar för att motverka bristande tillgänglighet - Claesson,Manuella; Nåvall-Palm,Elly (2026)
In 2015, lack of accessibility was introduced as a separate form of discrimination in the Swedish Discrimination Act. The reform aimed to improve access to employment for people with disabilities. Despite this change, statistics show that large differences in employment, work capacity and experiences of discrimination remain compared to the rest of the population. This raises important legal questions about how employers’ duties to adapt the workplace have developed over time and how far these duties extend in practice. The purpose of the thesis is to examine the legal development of disability discrimination, with a particular focus on the employers’ obligations to provide reasonable support and workplace adaptations. Using the legal dogmatic method, the study analyses how international and European legal frameworks, such as the Convention on the Rights of Persons with Disabilities (CRPD), the Employment Equality Directive and the EU Charter of Fundamental Rights, have influenced Swedish law. The thesis also examines the legal requirements for lack of accessibility under the Swedish Discrimination Act and how they are applied in court practice. The study is limited to working life and covers the legal relationship between employers, employees, job applicants and vocational trainees. An analysis of 19 judgements from the Swedish Labour Court shows how courts assess what counts as reasonable accommodation in practice. Special attention is given to cases AD 2010 No. 13 and AD 2017 No. 51, which have also been criticized by the CRPD Committee. The thesis shows that employers’ responsibilities to adapt the workplace have become stronger over time and that the focus has shifted from the individuals’ limitations to barriers in the work environment. At the same time, there is still a large degree of uncertainty in how reasonableness is assessed, especially when employers encounter financial or practical difficulties. The conclusion is that current legal practice seeks to balance flexibility with legal certainty.
Keywords: Bristande tillgänglighet; diskriminering på grund av funktionsnedsättning; arbetsgivarens anpassningsskyldighet; skäliga anpassningsåtgärder; arbetsrätt; diskrimineringslagen; funktionsnedsättning i arbetslivet. Lack of accessibility; discrimination based on disability; employer’s obligation to provide reasonable accommodation; reasonable accommodation measures; labour law; discrimination law; disability in working life.